Digitalization and Forestry: Technologies for the Preservation of Tropical Forests - Sembiring, Tamaulina Br.; Rosalia, Olyvia (PT. Anagata Sembagi Education, 2025)
This research explores how digital tools are reshaping efforts to preserve Indonesia’s tropical forests, focusing on technologies like drones, satellite monitoring, and IoT sensors. Employing a qualitative case study methodology complemented by detailed interviews, the study reveals that digital innovations significantly enhance forest oversight by boosting data precision, enabling quicker wildfire alerts, and streamlining inter-agency collaboration. Despite these advancements, critical obstacles remain, including inadequate digital infrastructure, limited tech know-how among local populations, and policy disconnects between national and regional authorities. The study also underscores the vital role of empowering local communities through education and accessible technology to foster active participation in conservation. Ultimately, successful integration of digital solutions depends on flexible governance frameworks and capacity-building initiatives that collectively drive sustainable ecological, social, and economic benefits. The insights gathered are intended to guide the formulation of more impactful and enduring tropical forest conservation policies in Indonesia.